2013
DOI: 10.1002/ange.201307520
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Compelling Biomimetic Metal–Organic Framework Catalyst for the Degradation of Nerve Agent Simulants

Abstract: Inspired by biology, in which a bimetallic hydroxide‐bridged zinc(II)‐containing enzyme is utilized to catalytically hydrolyze phosphate ester bonds, the utility of a zirconium(IV)‐cluster‐containing metal–organic framework as a catalyst for the methanolysis and hydrolysis of phosphate‐based nerve agent simulants was examined. The combination of the strong Lewis‐acidic ZrIV and bridging hydroxide anions led to ultrafast half‐lives for these solvolysis reactions. This is especially remarkable considering that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
90
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(90 citation statements)
references
References 48 publications
(42 reference statements)
0
90
0
Order By: Relevance
“… and which emphasizes their advantage as protective materials at ambient conditions. Even though other studies have reported the fast hydrolysis of the organophosphate in MOF, it was achieved by a direct contact of MOF with the simulant. In our study, we report the mineralization of DMCP vapors.…”
Section: Resultsmentioning
confidence: 99%
“… and which emphasizes their advantage as protective materials at ambient conditions. Even though other studies have reported the fast hydrolysis of the organophosphate in MOF, it was achieved by a direct contact of MOF with the simulant. In our study, we report the mineralization of DMCP vapors.…”
Section: Resultsmentioning
confidence: 99%
“…NU-1000 and NU-1000-dehyd represent the fastest known phosphoester-containing hydrolysis catalysts so far: 3 times and 30 times faster than found in our previous work with UiO-66 (ref. 10), and 20 times and 200 times faster than the well-known Cr-MIL-101, which contains coordinatively unsaturated Cr III ions linked by benzene dicarboxylates 20 . NU-1000 is also the fastest known MOF-based catalyst for the hydrolysis of GD (Table 1, bottom): 80-fold faster than the MOF HKUST-1 (under similar conditions and 960-fold faster in our buffered solution) which contains Cu II paddlewheel-based nodes and trimesic acid linkers 21 .…”
mentioning
confidence: 97%
“…For example, using the well-known twelve-connected Zr 6 -based MOF UiO-66, we were able to catalytically hydrolyse the nerve agent simulant dimethyl 4-nitrophenyl phosphate (DMNP, see Fig. 2a) 10 . Given their known outstanding thermal 11 , mechanical 12 and hydrolytic stabilities 13 , MOFs containing Zr 6 nodes and multitopic carboxylated linkers are among the most promising classes of potentially catalytic materials for deployment in personal chemical protection.…”
mentioning
confidence: 99%
“…A very recent publication focuses on the field‐effect chemical sensors using UiO‐66‐NH 2 for nerve agent (alkyl phosphonate, DMMP) detection . The [Zr 6 O 4 (OH) 4 ] 12+ cluster of the UiO‐66 type materials has been of specific interest because of its remarkably high activity toward phosphate ester hydrolysis . Signal transduction was achieved by monitoring the work function shift of UiO‐66‐NH 2 ‐coated electrodes upon exposure to ppb‐level (down to 3 ppb) concentrations of the target simulant.…”
Section: Trace Gas Enrichment and Sensingmentioning
confidence: 99%